Physical activity levels improve following discharge in people admitted to hospital with an acute exacerbation of chronic obstructive pulmonary disease - Tsai, Ling Ling Y (Chron Respir Dis, 2015)
This study aimed to determine the physical activity level of people admitted to hospital with an acute exacerbation of chronic obstructive pulmonary disease (AECOPD) and whether physical activity changed immediately after discharge and 6 weeks post hospital admission. In this prospective observational study, people admitted to hospital with an AECOPD had physical activity levels monitored using the SenseWear(®) Armband (model MF-SW) for 3 days in hospital (T1), during the first week at home following discharge (T2), and at home during the sixth week after admission (T3). Fifty participants (mean age (SD) 71 (10) years) completed the study. There was a linear increase in average steps per day over the three time periods (T1, mean (SD) 1385 (1972) steps/day; T2, 2040 (2680); T3, 2328 (2745); analysis of variance (ANOVA) p = 0.001) and time spent in moderate activity (3.0–6.0 metabolic equivalents; minutes/day) (T1, mean (SD) 16 (27) minutes/day; T2, 32 (46) minutes/day; T3, 35 (58) minutes/day; ANOVA p = 0.008). For both outcomes, post hoc t-tests showed significant improvements from T1 to T2 and from T1 to T3, but not between T2 and T3. Physical activity was low in hospital and significantly improved in the week after discharge but showed no further significant improvement at 6 weeks following a hospitalized AECOPD.